Andean Solanaceae species with resistance to biotic factors, such as tree tomato (Solanum betaceum Cav.) rootstocks - Pablo Viteri-Díaz; Wilson Vásquez-Castillo; Mauricio Racines-Oliva; William Viera-Arroyo (Manglar)
The infestation of the root system by nematodes (Meloidogyne incognita) and Fusarium solani to the rootneck hinders the production of tree tomato (Solanum betaceum Cav.), an Andean native fruit consumed in Ecuador and other countries. This paper evaluates the potential of different Ecuadorian Andean Solanaceae species (Solanum auriculatum, Solanum asperolanatum, Solanum arboreum and Nicotiana glauca), such as tree tomato rootstocks towards Fusarium and nematode resistance through controlled inoculation trials. The experimental design used was complete randomized in factorial arrangement with three factors. The variables were: fungus incubation time, incidence and lesion size, increase in nematode population, plant height increase and plant fresh weight. The most promising results for an extended open field evaluation were N. glauca (no incidences of Fusarium and 0.36 times increase in nematode population), followed by S. auriculatum. Fruit of these plants were assessed for chaconine and solanine content. The results indicated that the two rootstocks did not induce toxic substances in the fruits, they are suitable for commercial production zones, enhance crop yield, increase productive plant life and use fewer chemicals to control soil pathogens.